Attendance System By Implementing Arduino Microcontroller - Amin, Muhammad; Kurniawan, Heri; Sari, Della (Cattleya Darmaya Fortuna, 2024)
The attendance system is an important element in managing employee or student attendance in various institutions. The application of modern technology, such as the Arduino microcontroller, can improve efficiency and accuracy in recording attendance. Traditional attendance systems that use manual methods are often prone to errors in recording and data manipulation. This can lead to inaccuracies in attendance data and inappropriate decision making. This study aims to design and develop an Arduino microcontroller-based attendance system that can improve the accuracy and efficiency of attendance recording. This system is expected to minimize errors and data manipulation that commonly occur in manual attendance methods. The methods used in this study include the design, development, and testing stages of the system. The system is designed using an Arduino microcontroller connected to a sensor or identification module, such as RFID or fingerprint, to detect attendance. The results of the study show that the Arduino-based attendance system can increase the speed and accuracy of attendance recording compared to the manual method. This system also provides convenience in managing attendance data and can be integrated with existing management information systems. Implementation of this system can reduce the time and costs required to manage attendance effectively.